Deceptive Product Fulfillment, Trust Violation, and Consumer Platform Switching - Putri Rahayu; Ratna Komala Putri (Inovasi Analisis Data, 2026)
Purpose – This study investigates how deceptive product fulfillment influences consumer platform switching in digital marketplace platforms. Specifically, it examines the effects of product misrepresentation, information asymmetry, seller opportunism, and marketplace promise breach on switching behavior through post-purchase trust violation. Design/methodology/approach – The study adopts a quantitative explanatory survey design using a structured questionnaire. Regression and mediation analyses were applied to examine direct and indirect relationships among deceptive fulfillment perceptions, trust violation, and consumer platform switching. Findings – The findings show that product misrepresentation, information asymmetry, seller opportunism, and marketplace promise breach increase post-purchase trust violation. Trust violation subsequently increases consumer platform switching, confirming its central role in explaining post-purchase behavioral responses. Product misrepresentation and seller opportunism also exert direct effects on switching behavior, whereas information asymmetry and marketplace promise breach operate mainly through trust violation. Originality/value – This study integrates product deception, trust violation, and platform switching into a unified model of e-commerce behavior. It extends post-purchase research beyond satisfaction-based explanations and offers a platform governance perspective on how deceptive fulfillment damages consumer trust and encourages switching behavior.